ANALYSIS AND SIZING OF CRITICAL DRAINAGE POINTS ON JOAQUIM BATISTA DE OLIVEIRA AVENUE IN THE MUNICIPALITY OF FORMOSO DO ARAGUAIA - TO: A STUDY FOR MITIGATION OF FLOODING PROBLEMS (REMUNOM, 2025)
This study aims to analyze and measure critical urban drainage points on Joaquim Batista de Oliveira Avenue, located in the municipality of Formoso do Araguaia – TO, in order to propose solutions to mitigate recurring flooding problems. The research was motivated by disorderly urban growth, which resulted in soil impermeability and a consequent increase in surface runoff. Hydrological and hydraulic modeling methods were used, as well as tools such as Google Earth Pro, Plúvio 2.1 and Hidro Terraço 1.0, to collect data and calculate maximum flow at the points analyzed. The results demonstrated the need to install storm drains to efficiently capture rainwater. The study also discussed the concepts and components of micro and macro drainage systems, in addition to presenting sustainable alternatives, such as eco-paving and green roofs. It is concluded that efficient planning and the use of appropriate technologies are essential to ensure safety, sustainability and quality of life in urban areas.